KONTRIBUSI USAHATANI LAHAN PEKARANGAN TERHADAP EKONOMI RUMAH TANGGA PETANI DI KECAMATAN KERINCI KABUPATEN PELALAWAN - Roza Yulida (Indonesian Journal of Agricultural Economics, 2012)
The use of yard as one solution for the community to add the family income. Besides, itcan be as a source of food, preserve the environment and beautify the yard. The purpose ofthis study was to determine: (1)the contributionof farm yard to the household economics,and (2) the effect of farm yard’s income to the farmers’ household economics. The randomsampling method was used in this research to take 30 respondents as sample. The resultsshowed that: (1) There is an additional income of farming households in their yards. Theaverage income earned by farmers Rp.101.920, 00/harvesr. Income households beforerunning the program is Rp.2.177.731, 00/month and increased to Rp.2.279.651,00/month orcontributed by 4.47%; (2) Based on the analysis of the t test, t value is 3,47, while the valueof the t table is 2,045 with a significant level of α = 0.05 and 95% confidence level that (tcount> t table), therefore H1 is accepted, Ho is rejected. It means that the income offarmers’ household greater after implementing the program than before implementing theprogram. Therefore, there is a significant effect of each activity in the farmers who grewtheir yards on household income.Keywords: farmers’ income, household economics, farm yard